Understanding educator-mediated conflict resolution in a preschool environment: the experiences and feelings of preschool educators - Cakwe, Mandisa (Rhodes University, Faculty of Humanities, Department of Psychology, 2006)
This thesis discusses the experiences and feelings of preschool educators when resolving situations of conflict between preschool children. Data was collected by means of semistructured individual interviews with preschool educators and a video recorder recording conflict situations among preschool children focusing on educator resolution strategies. Grounded theory was used as a data analysis technique to analyse the data collected. The analysis revealed that the preschool educators under study do not use mediation as a conflict resolution strategy but use various strategies that include, prevention, directive approach, arbitration, myths and threats and rules. Data analysis also revealed that these preschool educators encounter experiences and feelings before, while and after intervening in the conflict situations of children. These findings imply that preschool educators lack the professional skill of conflict resolution. This suggests an urgent need of restructuring of the preschool educator's training to include conflict resolution training as one of their important component. Educators and parents also need to be consulted or involved in the process of restructuring the training.
Keywords: Education, Preschool; Early childhood education; Preschool children; Conflict management